Nonlinear finite element analysis of short and long reinforced concrete columns confined with GFRP tubes. (July 2017) - Hussein Abdallah, Maha; Shazly, Mostafa; Mohamed, Hamdy M; Masmoudi, Radhouane; Mousa, Ahmed
This paper presents three-dimensional nonlinear finite element models to understand the uniaxial behavior of concrete-filled fiber reinforced polymer tubes. A stress–strain confined model was introduced for the concrete, a damage criteria based on Hashin's failure model was used to model damage and failure of GFRP tubes, and steel bars were modeled based on classic metal plasticity model. A comparison between experimental results found in the literature and the finite element model was conducted regarding the load-deflection curves and the failure pattern of different test specimens. The model was found to be efficient in capturing the loads and deformations of slender concrete-filled fiber reinforced polymer tube columns. It was then used in a parametric study to understand the effect of different parameters (including fiber orientation, number of layers of (glass-fiber reinforced polymer) and steel reinforcement ratio) on the behavior of concrete-filled fiber reinforced polymer tube under axial compressive loading. It was observed that the behavior of the columns was greatly affected by the investigated analysis parameters.